Measurement of 34S/32S Ratios of NBS 120c and BCR 32 Phosphorites Using Purge and Trap EA‐IRMS Technology. Issue 1 (23rd July 2014) - Fourel, François; Martineau, François; Seris, Magali; Lécuyer, Christophe
<x xml:space="preserve">Abstract</x> Measurements of sulfur stable isotope ratios (34S/32S) have suffered from technical difficulties in analysing low‐S materials reducing their use despite their undeniable scientific interest. The measurement of 34S/32S ratios is a powerful tool for deciphering problems such as determining the sources of environmental pollutants, to detect adulteration, tracking the evolution of the redox state of the oceans and quantifying the role of the bacterial activity in sulfide minerals genesis. We have used a high‐precision method of sulfur isotope determination using a new type of elemental analyser based on 'purge and trap' technology. This new technique demonstrates the high quality of 34S/32S measurements for samples with S concentrations lower than 1% m/m. International calibrated references of diverse sulfur‐bearing materials were used to calibrate two low (< 1%) S‐bearing phosphorites used as compositional reference material for future use as isotopic references: BCR 32 and NBS 120c. δ34SCDT values of, respectively, 18.2‰ (1s = 0.3; n = 23) and 18.3‰ (1s = 0.4; n = 20) are proposed for these. Calibration of both phosphorites with international reference materials led to calculation of a mean standard error close to 0.4‰. The demonstration of a capability to reliably measure S isotope ratios in low‐S phosphate minerals or rocks opens up new fields of palaeoenvironmental reconstructions.